Geometry assessment of a sloped type wave energy converter - Gianmaria Giannini (2021)
Oscillatory wave energy converters of the sloped type may allow absorbing power from ocean waves efficiently if a valid optimal design is used. In earlier studies, the optimized geometry for the CECO device was defined by implementing a simplified frequency-domain model. In this paper, that geometry is evaluated against the former one by taking into consideration a more realistic modelling approach and assessment scenario. The two geometries were benchmarked through a time-domain model, which allows taking into account realistic sea states and the use of end-stops to limit the amplitude of CECO motions. It was concluded that the optimized geometry allows extra energy production for most of the irregular sea states evaluated (45% more annual energy production). Performance indices were also used to compare the two geometries and it was concluded that the optimized geometry was particularly advantageous for the more energetic sea states. Overall, this study clearly shows that the choice of the generator rated power and end-stops span length are key aspects in determining realistically the annual energy production of sloped-motion wave energy converters. ? 2021 Elsevier Ltd. All rights reserved.